THU0197 Conventional Dmard Therapy and Improvement of Disease Activity in A Cohort of Rheumatoid Arthritis Patients Treated under Treat To Target Recommendations. (15th July 2016) - Santos-Moreno, P.; Villarreal, L.; Ballesteros, G.; Bello, J.; Castillo, E.; Giraldo, R.; Gomez, D.; Aza, A.; Lopez, A.; Cardozo, A.; Palacio, N.; Castro, C.; et al.
Abstract : Background: Treat to Target (T2T) strategy becomes from the need to develop therapeutic targets and tools to achieve defined outcomes in rheumatoid arthritis (RA). This strategy is being used last years in Colombia. On the other hand a multidisciplinary care team (MCT) model was generated in order to improve outcomes. Objectives: The aim of this study was to describe global change in Disease Activity Score 28 (DAS28) using T2T strategy for a 24-month period in patients with conventional DMARD therapy in a large cohort of patients from a Colombian specialized in RA center with a MCT model. Methods: A descriptive retrospective study was performed. Records of patients using conventional DMARD treatment from specialized in RA center were reviewed; those patients were followed-up under T2T standards. Clinical follow-up was according to DAS28 as follows: every 3–5 weeks (DAS28 >5.1), every 7–9 weeks (DAS28 ≥3.1 and ≤5.1), and every 11–13 weeks (DAS28 <3.1). Therapy had to be adjusted with DAS28 >3.2 unless patient's conditions don't permit it. A MCT model means that a patient should be seen by other specialties such as physiatrist, physical and occupational therapy, nutritionist and psychologist at least 3 times a year. We divided patients in three groups: low disease activity (LDA), moderate disease activity (MDA) and severe disease activity (SDA) patients and the aim of the study was to look at what percentage of patients who were in moderate or severe disease activity reached a low disease activity or remission (REM). Descriptive epidemiology was done, percentages and averages were calculated; the median of each variable was analyzed using t-Student assuming normality for DAS28 distribution and the level activity disease was analyzed using Pearson's statistics. Results: 767 patients were included in this study, 615 (80%) women and 152 (20%) men. Average age was 63 ± 11 years. Concerning to treatment of entire cohort, 76 (6.8%) patients were using Leflunomide alone, 47 (6%) and Metothrexate alone, 164 (21%) Leflunomide plus Metothrexate, 43 (6%), Leflunomide plus other DMARDs, 84 (11%), Metothrexate plus others DMARDs 168 (22%) and 261 (34%) "only" DMARDs without Leflunomide or Metothrexate. At 24 months was observed an increase in percentage of patients in remission/LDA (up to 85%) and a decrease in percentage of patients in MDA/SDA disease activity statistically significant. At beginning DAS28 was 4.07 ± 1.03 and after 24 months of follow-up DAS28 was 2.7 ± 0.72, showed improvement (p<0.00). Conclusions: There is a global improvement of DAS28 in a cohort of RA patients receiving only conventional therapy, treated and followed under T2T strategy recommendations and a MCT model. We show real-world data on conventional DMARD utilization in patients with RA in a low income developing country, these observations could be used by decision makers in order to consider health decisions. Disclosure of Interest: None declared